2023
DOI: 10.32479/ijeep.14030
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Education and Green Supply Chain Practices in Achieving Sustainable Development: Evidence from Indonesia

Abstract: Globally, environmental education and green supply chain (GSC) practices are considered essential elements for sustainable development, and this aspect needs new literature and policymakers' attention. Hence, the present article examines the impact of GSC practices on the sustainable development of manufacturing organizations in Indonesia. The article also investigates the moderating role of environmental education among green purchasing, IEM, and sustainable development in manufacturing organizations in Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Not in line with researchers' expectations, these findings explain that GHRM among food processing SMEs owners does not have a significant direct effect on OCBE (H4). Although previous studies have reported a strong relationship between GHRM on OCBE [28][29][30][31][32][33]. Therefore this study failed to identify this relationship, but these findings are in line with the findings [21] which found that GRHM did not affect the OCBE of hotel employees in Vietnam.…”
Section: Direct Effectsupporting
confidence: 68%
See 2 more Smart Citations
“…Not in line with researchers' expectations, these findings explain that GHRM among food processing SMEs owners does not have a significant direct effect on OCBE (H4). Although previous studies have reported a strong relationship between GHRM on OCBE [28][29][30][31][32][33]. Therefore this study failed to identify this relationship, but these findings are in line with the findings [21] which found that GRHM did not affect the OCBE of hotel employees in Vietnam.…”
Section: Direct Effectsupporting
confidence: 68%
“…Other empirical studies also explain that GHRM practices have a positive and significant effect on OCBE [33]. Furthermore, GHRM does not only play a role in increasing employee OCBE but GHRM also plays a role in improving EP as studies [24][25][26][27][28][29][30][31][32][33][34] that organizations that wish to employ applicants first ask several questions related to the environment during the interview session and will select applicants with strong environmental values, then with these candidates organizations can improve their EP. This finding is in line with studies [23][24][25][26][27] that GHRM practices are critical to EP.…”
Section: Green Human Resource Management (Ghrm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia is crucial to achieving sustainable development in Southeast Asia (Tiawon & Miar, 2023). Environmental education is recognized by the country as being vital for promoting sustainable development and conservation practices (Charina et al, 2022;Parmawati et al, 2023). Indonesia's role in achieving education for sustainability is to promote quality education that incorporates knowledge, ethics and values related to sustainable development (Sr Yuliani & Hartanto, 2020).…”
Section: Figure 3 Ranking Of Stem-esd Research Countries/regionsmentioning
confidence: 99%